PENERAPAN MODEL PEMBELAJARAN PROJECT WORK DENGAN PERBAIKAN JOB SHEET UNTUK MENINGKATKAN HASIL PRAKTIK SISWA KELAS XII DI SMKN 1 MANGGAR - EDY YUNARSAH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
Learning is a process of change that occurs in a person through reinforcement so that permanent changes occur. The changes produced by the learning process are progressive and accumulative leading to perfection, for example from not being able to being able, from not understanding to understanding, both covering aspects of knowledge (cognitive domain), affective aspects (affective domain) and psychomotor aspects (psychomotoric domain). Based on the results of observations made, it is known that student learning outcomes in the subject of light vehicle engine maintenance for basic competence in regular maintenance of conventional gasoline fuel systems are still low, especially practical learning outcomes. Therefore, classroom action research was conducted through the application of the Project work learning model with the improvement of job sheets with the aim of improving practical learning outcomes for class XII-B TKRO SMKN 1 Manggar students. The research procedure was carried out using 2 cycles where each cycle was carried out in accordance with the learning organization strategy with the changes to be achieved. The steps for implementing the research were carried out in four stages, namely 1) action planning, 2) action implementation, 3) observation, and 4) reflection for the next cycle. The research data showed an increase in practical learning activities from 19.3% pre-cycle or 6 students completed from 31 students in the competent category (grades 75 to 86) and in the first cycle there was an increase of 64.5% 20 students completed (6 students were very competent, 14 students are competent) while in cycle II of 31 students there are 28 students who have completed an increase (10 students are very competent, 18 students are competent) or 90.3%. Based on research data in cycle I and cycle II of 31 students of class XII-B TKRO the application of the project work learning model with job sheet improvements can improve practical learning outcomes. ABSTRAKBelajar merupakan proses perubahan yang terjadi pada diri seseorang melalui penguatan (reinforcement) sehingga terjadi perubahan yang bersifat permanen. Perubahan yang dihasilkan oleh proses belajar bersifat progresif dan akumulatif mengarah kepada kesempurnaan, misalnya dari tidak mampu menjadi mampu, dari tidak mengerti menjadi mengerti, baik mencakup aspek pengetahuan (kognitive domain), aspek afektif (afektive domain) maupun aspek psikomotorik (psychomotorik domain). Berdasarkan hasil pengamatan yang dilakukan diketahui bahwa hasil belajar siswa pada mata pelajaran pemeliharaan mesin kendaraan ringan untuk kompetensi dasar merawat berkala sistem bahan bakar bensin konvensional masih rendah khususnya hasil belajar praktik. Oleh karena itu dilakukan penelitian tindakan kelas melalui penerapan model pembelajarn Project work dengan perbaikan job sheet dengan tujuan untuk meningkatkan hasil belajar praktik siswa kelas XII-B TKRO SMKN 1 Manggar. Prosedur penelitian dilakukan dengan menggunakan 2 siklus dimana tiap siklus dilaksanakan sesuai dengan strategi pengorganisasian pembelajaran dengan perubahan yang ingin dicapai. Adapun langkah pelaksanaan penelitian dilakukan melalui empat tahap, yaitu 1) perencanaan tindakan, 2) pelaksanaan tindakan, 3) observasi, dan 4) refleksi untuk siklus selanjutnya. Data hasil penelitian adanya peningkatan aktivitas belajar praktik dari pra-siklus 19,3 % atau 6 siswa tuntas dari 31 siswa kategori kompeten ( nilai 75 s.d. 86) dan pada siklus I ada peningkatan 64,5 % 20 siswa tuntas ( 6 siswa sangat kompeten, 14 siswa kompeten) sedangkan pada siklus II dari 31 siswa terdapat 28 siswa tuntas mengalami peningkatan (10 siswa sangat kompeten, 18 siswa kompeten) atau 90,3 %. Berdasarkan data penelitian pada siklus I dan siklus II terhadap 31 siswa kelas XII-B TKRO penerapan model pembelajaran projeck work dengan perbaikan job sheet dapat meningkatkan hasil belajar praktik.